Generic Promotion of Sorghum for Food and Industrial Uses. Issue 1 (1st January 2020) - Williams, Gary W.; Capps, Oral
Abstract: Globally, over half of all sorghum is used for human consumption. Yet sorghum is largely unknown as a food in the United States and other developed countries. Recently, the U.S. demand for sorghum as a gluten-free, non-GMO input to food products has been growing. At the same time, the use of sorghum for food and industrial uses is being promoted by the producer-financed United Sorghum Checkoff Program (USCP). How much of that growth can be attributed to the USCP promotion? Has the investment been profitable for sorghum producers? This study finds that USCP promotion programs have resulted in a 4% increase in the sales value of sorghum for that purpose and a 1% increase in total sorghum farm revenue. The farm level benefit-cost ratio is estimated at between 5.8 and 7.1 in terms of producer profit per dollar spent on promotion.